What times what times what equals 66

Answers

Answer 1
Answer: The answer is 11 x 6=66
That 11, 6, and 1 are some of the factors of 66. 
So we use 11 and 6 and we get 66. 
This is only the easiest factors we can multiply. 
There are many more factors that you can multiply together and get 66. 

Answer 2
Answer:

The combinations of three numbers that multiply to give 66 are (1, 2, 33), (1, 3, 22), (1, 6, 11), and (2, 3, 11). that is 1 × 2 × 33 = 66, 1 × 3 × 22 = 66, 1 × 6 × 11 = 66, 2 × 3 × 11 = 66.

What is multiplication

Multiplication is an arithmetic operation that combines two or more numbers to find their product. When you multiply two numbers, you are essentially adding one number repeatedly to itself a certain number of times.

For example, if you multiply 3 by 4, it means adding 3 to itself four times:

3 × 4 = 3 + 3 + 3 + 3

= 12

In multiplication, the numbers being multiplied are called the multiplicand and the multiplier. The result of the multiplication is called the product.

5 × 6 = 5 + 5 + 5 + 5 + 5 + 5 = 30

2 × 9 = 2 + 2 + 2 + 2 + 2 + 2 + 2 + 2 + 2 = 18

7 × 3 = 7 + 7 + 7 = 21

Multiplication can be performed with any real numbers, including whole numbers, fractions, decimals, and even negative numbers. The basic principles and properties of multiplication remain the same regardless of the numbers being multiplied.

Learn more on multiplication here brainly.com/question/10873737

#SPJ6


Related Questions

How many milliliters of water are in each 7 beakers
A company that makes steel girders can produce 6 tons of girders in one day. How many pounds is this?
Which is a factor of 76? A.4B.14C.8D.12
Determine the quotient of 1 and 2 over 3 divided by 4 over 5. 1 and 1 over 3 1 and 8 over 15 2 and 1 over 12 2 and 5 over 6
An 18% alcohol solution is mixed with a 45% alcohol solution to produce 12 ounces of a 36% alcohol solution. How many ounces of the 18% solution and the 45% solution must be used?

Sin(2x - 3) = cos(4x - 30
A)
26.33°
29.330
60.67°
D)
63.679

Answers

Answer:

D

Step-by-step explanation:

Given p(x)=3x^5+2x^2-5, what is the value of the function at -5/3

Answers

Answer:

-(3080)/(81)

Step-by-step explanation:

The given function is:

p(x)=3x^(5)+2x^(2)-5

We have to find the value of the function at x = -5/3

In order to do this we need to replace every occurrence of x in the given function by -5/3. i.e.

p(-(5)/(3))=3(-(5)/(3))^(5)+2(-(5)/(3) )^(2)-5\n\n p(-(5)/(3))=3(-(3125)/(243) )+2((25)/(9) )-5\n\np(-(5)/(3))=-(3125)/(81)+(50)/(9)-5\n\n p(-(5)/(3))=-(3080)/(81)

Thus, the value of the function at x =-5/3 is -(3080)/(81)

5/12-3/20 use the least common multiple as the denominator

Answers

The common multiple of 12 and 20 is 60.
You've got to multiply the first one by 5 and the second by 3.
5*5= 25
This therefore becomes 25/60
The second becomes 3*3= 9
This becomes 9/60
As you're subtracting, you only subtract the numerators.
25-9= 16
Therefore, the answer is 16/60 which can be simplified to 4/10 or 2/5
Hope this helps :) 

when buying a new car you have a choice of 4 different models 3 different colors and either compact or family how many choices are there for one car?

Answers

4x3x2 is your answer so......24

Must the difference between 2 rational numbers be a rational number?

Answers


Yes.  The difference between 2 rational numbers must be a rational number.

The first rational number can always be written as a fraction of integers.
Let's call it   A/B .

The second rational number can always be written as a fraction of integers.
Let's call that one  C/D .

       Their difference is        A/B  -  C/D .

       'BD' is a common denominator.

       A/B  =  AD/BD

       C/D  =  CB/BD

       A/B - C/D  =  AD/BD  -  CB/BD  =

                                      (AD - CB) / BD

Each term in that ugly thing  /\  is a product of integers,
so it must be must be another integer.

Therefore the whole ugly fraction is another rational number.

a/b - c/d with a,b,c,d as integers and b,d ≠ 0. a/b - c/d -> ad/bd - bc/bd --> (ad - bc)/bd
The difference will always be rational. This is because the denominator will never be 0. Everything is closed under some kind of operation, and the answers will always be able to be written as a ratio.
Hope that helped.

What is the answer to 2x+4-3x=0

Answers

2x+4-3x=0
   -4       -4
2x-3x=-4
-1x=-4
_      _
-1    -1
x=4
so the answer is x=4
2x + 4 -3x = 0

2x - 3x  + 4 = 0
-x + 4 = 0  
    -4   = - 4
-x = - 4
x = 4 

Ans : x = 4